2016
DOI: 10.2134/jeq2015.03.0121
|View full text |Cite
|
Sign up to set email alerts
|

Soil Carbon and Carbon/Nitrogen Ratio Change under Tree Canopy, Tall Grass, and Turf Grass Areas of Urban Green Space

Abstract: Soils in urban green spaces are an important carbon (C) store, but urban soils with a high carbon to nitrogen (C/N) ratio can also buffer N eutrophication from fertilizer use or atmospheric deposition. The influence of vegetation management practices on soil C cycling and C/N ratios in urban green spaces is largely unknown. In 2013, we collected replicate (n = 3) soil samples from tree canopy, tall grass, and short turf grass areas (n = 3) at four random plot locations (n = 4) established in 13 golf courses (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
37
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 39 publications
6
37
1
Order By: Relevance
“…Our second hypothesis, predicting that park age affects the biochemistry of the soil, was also supported. In particular, young park soils contained lower concentrations of OM, tot-C, and tot-N. Our results are also in agreement with previous findings that the accumulation of C in park soils diminishes with soil depth (Golubiewski, 2006;Raciti et al, 2011;Edmondson et al, 2014a,b;Bae and Ryu, 2015;Livesley et al, 2016). However, as the stratification of these soil variables did not relate to park age, our third hypothesis is not supported.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Our second hypothesis, predicting that park age affects the biochemistry of the soil, was also supported. In particular, young park soils contained lower concentrations of OM, tot-C, and tot-N. Our results are also in agreement with previous findings that the accumulation of C in park soils diminishes with soil depth (Golubiewski, 2006;Raciti et al, 2011;Edmondson et al, 2014a,b;Bae and Ryu, 2015;Livesley et al, 2016). However, as the stratification of these soil variables did not relate to park age, our third hypothesis is not supported.…”
Section: Discussionsupporting
confidence: 88%
“…For example, Bae and Ryu (2015) observed that mixed forests had the highest SOC stocks, followed by evergreen and broadleaf forests, and lawn in an urban park in Seoul, Republic of Korea. Similarly, in a study of 13 urban green spaces (golf courses) in Melbourne, Australia, Livesley et al (2016) reported that tree-canopy areas had higher concentrations of C and N than nearby grassy areas. These studies suggest that woody plants can enhance C sequestration in urban soils.…”
Section: General Effects Of Plant Functional Groups On Urban Park Soilsmentioning
confidence: 93%
See 3 more Smart Citations